Separasi Garam Natrium dan Protein pada Putih Telur Asin Menggunakan Membran Ultrafiltrasi - Paradigma, Hening; Sitanggang, Azis Boing; Budijanto, Slamet (Jurnal Teknologi dan Industri Pangan, 2024)
Salted egg white desalination is a method of reducing salt levels while optimising protein yield. This study aimed to analyse the effects of membrane pore size and dilution levels on the quantity of protein and salts. The identification of rheological properties and the type of fouling that occurs during the salted egg white desalination process were also examined. The sample with the most effective desalination result was analysed for the variation of amino acid profiles before and after filtration. A completely randomised design was employed in this study, with treatment factors of membrane pore size (5, 10, and 20 kDa) and dilution levels (undiluted and 5-time dilution) with two replications. Filtering salted egg whites at each pore size of the ultrafiltration membrane retained all the proteins in the salted egg whites. Furthermore, varying the dilution level had no effect on the protein loss. The permeation weight was positively correlated with the desalination level. The fouling model simulation successfully identified the cake filtration model, with the rheological characteristics of salted egg white before and after filtration exhibiting shear thinning behaviour. The filtered salted egg whites, measured at a low shear rate, demonstrated a lower viscosity compared to sample than before filtration. The most effective treatment for salted egg white desalination was obtained by subjecting undiluted sample with 20 kDa-membrane filtration. Analysis of the amino acid profiles of the most effective treatment showed no significant changes after filtration.